SOSIALISASI PERMASALAHAN DAMPAK RADIASI GELOMBANG ELEKTROMAGNETIK MENARA TELEKOMUNIKASI DI PERMUKIMAN MASYARAKAT - Fitri Imansyah; Iqbal Arsyad; Usman A. Gani (Jurnal Abdi Insani, 2023)
In the era of rapidly developing technology, the use of telecommunications equipment and its supporting infrastructure is increasingly widespread. One of the people's concerns is the impact of electromagnetic wave radiation from telecommunication towers on health and the environment. This outreach activity aims to address the lack of accurate information and combat unfounded concerns about telecommunications technology. In its implementation, various approaches are used, such as outreach in the form of seminars and distribution of information materials. Creative methods such as interesting and interactive presentations are also applied to facilitate public understanding. The results of this activity show positive changes in people's understanding of electromagnetic wave radiation. Society now has better knowledge about safe radiation levels, mitigation measures that can be taken, and the need to use telecommunication technology wisely. Community support for mitigation measures, such as keeping a distance from telecommunication towers or using protective devices, has also seen an increase. In addition, this activity has a positive psychological impact by reducing unfounded fears and worries. Communities responded positively to socialization efforts and recognized the benefits of a better understanding of telecommunications technology. The ultimate goal of this activity is to create a society that is more aware, knowledgeable, and ready to take precautions against the effects of electromagnetic wave radiation. Thus, this socialization activity has a significant role in informing the public, changing understanding, supporting mitigation measures, and planning for a future that is safer and aware of the impact of electromagnetic wave radiation from telecommunication towers on residential communities.